Synthesis and SAR Studies of Isoquinoline and Tetrahydroisoquinoline Derivatives as Melatonin Receptor Ligands. (1st December 2021) - Ettaoussi, Mohamed; Laversin, Amélie; Vreulz, Brandon; Rami, Marouane; Lebegue, Nicolas; Delagrange, Philippe; Caignard, Daniel Henri; Melnyk, Patricia; Liberelle, Maxime; Yous, Saïd
Abstract: In our constant search for new successors of agomelatine, we report herein a new series of compounds resulting from bioisosteric modulation of the naphthalene ring. The isoquinoline and tetrahydroisoquinoline derivatives were synthesized and pharmacologically evaluated. This isosteric replacement of the naphthalene group of agomelatine has led to potent agonist and partial agonist compounds with nanomolar melatonergic binding affinities. Overall, the presence of a nitrogen atom was accompanied with a decrease in the binding affinity toward both MT1 and MT2 and the loss of 5HT2C response, especially for tetrahydroisoquinoline in comparison with the parent compound. Interestingly, due to the presence of this nitrogen atom, a notable improvement in the pharmacokinetic properties was observed for all compounds. Abstract : Successors of agomelatine : A series of isoquinoline and tetrahydroisoquinoline derivatives were shown to have good melatonergic affinity and no 5‐HT2C affinity. Compounds 38 and 43 demonstrated the most interesting binding affinities, whereas tetrahydroisoquinoline 23 showed 45‐fold MT2 selectivity over the MT1 receptor subtype.